2019
DOI: 10.1021/acs.bioconjchem.9b00095
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Functionalized Supramolecular Polymers: Dynamic Multicomponent Assemblies with Emergent Properties

Abstract: Recent years have witnessed an increasing interest in hybrid molecular systems in which the programmability of DNA hybridization is used to introduce enhanced molecular control in synthetic systems. The first examples of DNA-functionalized supramolecular polymers have been reported only recently, but have already revealed structural and functional properties that are not easily obtained in either synthetic supramolecular polymers or DNA-only based systems. In this Topical Review, we provide an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…[8][9][10][11][12] Merging purely artificial DNA nucleotide surrogates with natural DNA nucleotides lead to DNA conjugates and the resulting functional supramolecular assemblies have recently gained much attention in the fields of nanotechnology and materials science. [13][14][15][16][17][18][19] Such functional supramolecular polymers feature properties beyond the classical role of DNA in biological systems, with applications in optoelectronic devices, drug delivery systems, and diagnostics to name a few. [20][21][22][23][24][25][26][27][28] However, vesicular morphologies are predominantly reported from lipid-DNA conjugates or DNA functionalized liposomes, [29][30][31][32][33][34] while the field apart from lipid-based DNA constructs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Merging purely artificial DNA nucleotide surrogates with natural DNA nucleotides lead to DNA conjugates and the resulting functional supramolecular assemblies have recently gained much attention in the fields of nanotechnology and materials science. [13][14][15][16][17][18][19] Such functional supramolecular polymers feature properties beyond the classical role of DNA in biological systems, with applications in optoelectronic devices, drug delivery systems, and diagnostics to name a few. [20][21][22][23][24][25][26][27][28] However, vesicular morphologies are predominantly reported from lipid-DNA conjugates or DNA functionalized liposomes, [29][30][31][32][33][34] while the field apart from lipid-based DNA constructs remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Examples include the assembly of quasi-onedimensional fibrillar aggregates with tunable kinetic characteristics, hierarchical assemblies, and branched networks such as hydrogels and coacervates. [13][14][15] In addition, supramolecular polymers can be used as modular templates for the assembly of various biomolecules, including nanoparticles, 16,17 nucleic acids, 18,19 and proteins. [20][21][22][23] Recent work has revealed that intracellular signalling pathways heavily rely on the dynamic assembly of higher-order fibril-like aggregates that are structurally well-defined but open-ended and sometimes quasi-infinite.…”
mentioning
confidence: 99%
“…In particular, 1D assemblies of nucleic acids triggered widespread interest in the materials sciences for targeting functions beyond the obvious connection to biology. 23 For example, DNA can act as a versatile template for mineralization of various inorganic materials, providing access to nanoscale structures unattainable by other approaches. 24 The growth occurs via interactions of available negatively charged phosphate groups with suitable nucleation seeds followed by mineralization growth.…”
Section: One-dimensional Supramolecular Systemsmentioning
confidence: 99%